2023
DOI: 10.3389/fimmu.2023.1172710
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphila-Nlrp3 is involved in the neuroprotection of phosphoglycerate mutase 5 deficiency in traumatic brain injury mice

Abstract: IntroductionGut-microbiota-brain axis is a potential treatment to decrease the risk of chronic traumatic encephalopathy following traumatic brain injury (TBI). Phosphoglycerate mutase 5 (PGAM5), a mitochondrial serine/threonine protein phosphatase, resides in mitochondrial membrane and regulates mitochondrial homeostasis and metabolism. Mitochondria mediates intestinal barrier and gut microbiome.ObjectivesThis study investigated the association between PGAM5 and gut microbiota in mice with TBI.MethodsThe contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…This suggests that reduction in Akkermansia is exacerbated by high levels of colonic inflammation, which is seen in either combined age and burn injury or inflammatory bowel disease. A recent study demonstrated that Akkermansia is negatively associated with intestinal injury after traumatic brain injury (39), which agrees with our data showing that Akkermansia is negatively associated with intestinal barrier dysfunction (Fig. 3).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This suggests that reduction in Akkermansia is exacerbated by high levels of colonic inflammation, which is seen in either combined age and burn injury or inflammatory bowel disease. A recent study demonstrated that Akkermansia is negatively associated with intestinal injury after traumatic brain injury (39), which agrees with our data showing that Akkermansia is negatively associated with intestinal barrier dysfunction (Fig. 3).…”
Section: Discussionsupporting
confidence: 93%
“…In addition to being gut protective, Akkermansia colonization correlates negatively with neuroinflammation and neurological dysfunction after traumatic brain injury ( 39 ), primarily by decreasing inflammasome activation within the brain. Furthermore, increasing the amount of acetate, the primary short-chain fatty acid product of Akkermansia , after traumatic brain injury in experimental animals significantly improved motor performance ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Bacteroidota and Muribaculaceae were the dominant bacterial taxa in TBI mice, while FMT treatment could decrease the abundance of Bacteroidota and Muribaculaceae . Additionally, the study has shown the increased abundance of Muribaculum , the genus type of the family Muribaculaceae , order Bacteroidales , and phylum Bacteroidota in TBI mice ( Chen Y. et al., 2023 ). In addition, our results showed that FMT treatment decreased the relative abundances of Patescibacteria , Saccharimonadaceae , Rikenellaceae , Alistipes , Ruminococcaceae , and Eggerthellaceae in TBI mice, which was consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Akkermansia , belonging to the family Akkermansiaceae of the phylum Verrucomicrobiota , exerted anti-inflammatory effects ( Qu et al., 2021 ). The study has shown that the relative abundance of A. muciniphila was negatively correlated with intestinal injury and neurological dysfunction, as well as the levels of TNF-α and IL-1β in cortical tissue after TBI, and A. muciniphila treatment improved intestinal injury, neurological dysfunction, and neuroinflammation in the cerebral cortex of TBI mice ( Chen Y. et al., 2023 ). To sum up, the enrichment of inflammation-related bacteria, such as Rikenellaceae and Alistipes , and the reduction of anti-inflammatory-related bacteria Akkermansia might participate in the process of TBI, and these changes in the relative abundance of bacteria could be reversed by FMT, which contributed to the explanation of the specific therapeutic mechanism of FMT in TBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation